Açık Liderlik Ölçeğinin Geliştirilmesi - Polat, Murat; Arabacı, İmam Bakır (My University, 2016)
Bu araştırmanın amacı, sosyal medya temelli bir liderlik türü olan açık liderlik için örgütlerin açık liderlik seviyelerini ölçen geçerli ve güvenilir, likert tipi bir ölçek geliştirmektir. Araştırmanın çalışma grubunu Muş Alparslan Üniversitesinde görev yapmakta olan 176 akademik, 97 idari personel olmak üzere 273 katılımcı oluşturmaktadır. Ölçme aracının yapı geçerliğini tespit etmek amacıyla açımlayıcı (AFA) ve doğrulayıcı faktör analizleri (DFA); güvenirlik için ise Cronbach's Alfa katsayısı, madde toplam korelasyonları, İki Yarı Test (Spearman Brown) ve maddelerin alt ve üst % 27'lik gruplarda t-testi ile karşılaştırılması yapılmıştır. Nihai olarak ölçme aracının üç alt boyuttan ve 23 ifadeden oluştuğu; açıkladığı toplam varyansın ise %61,40 olduğu tespit edilmiştir. Açımlayıcı faktör analizinin ardından yapılan doğrulayıcı faktör analizine göre üç boyutlu ölçek yapısının iyi bir uyum verdiği bulunmuştur (X2/df1.96, RMSEA.06. RMR.06, NFI.97, CFI.98, IFI.98, RFI.97, AGFI.85, GFI.88). Ölçeğin güvenirlik analizi sonucunda iç tutarlılık katsayısının, ?.95 iki yarı test güvenirliğinin ise r.91 olduğuna ulaşılmıştır. Araştırma sonuçları, "Açık Liderlik Ölçeği (ALÖ)"nin üç boyutlu bir yapıda ve özellikle liderlik çalışmalarında kullanılacak türde geçerli ve güvenilir bir ölçme aracı olduğunu göstermiştir.

The purpose of this research is to develop a likert type scale which measures open leadership levels of organizations. The study group consists of 273 participants, 176 academic and 97 administrative personnel who work in Muş Alparslan University. For the analysis of data regarding the validity and reliability of the developed scale following analyses were conducted; content validity, construct validity, t-test for the significant difference between the item mean correlations of top and bottom %27 of the group, corrected item-total correlations, Cronbach Alpha internal consistency coefficients, and split-half test correlations (Spearman Brown). And in order to establish structural validity an exploratory factor analysis has been used and to ensure the factor selection was valid a confirmatory factor analysis was used. As a result of analysis, the draft scale consisted of 23 items and the total explained variance is %61.40. The subscales of the scale are determined as three factors: the acceptance of power and continuous sharing, curiosity to promote and accountability, effective use of social networking. These subscales are found to be consistent with the literature. And according to confirmatory factor analysis, model's fit index obtained via CFA was examined and Chi-square value (x2 438.39, n 273, sd223, p0.00) is observed to be significant. Fit index values are; RMSEA; 0.06, RMR; 0.06, GFI; 0.88, AGFI; 0.85, CFI; 0.98, IFI; 0.98, NFI; 0.97; x2/df 1.96). These values shows that the scale is a good model. For the realibility of the scale of whose internal consistency was analyzed, Cronbach Alpha value is estimated to be .095. Finally, evidences reached for validity and reliability show that the OLS can be validly and reliably used for measuring open leadership levels among organizations.
Development Of Open Leadership Scale
Keywords: Eğitim, Eğitim Araştırmaları